The coiled coil motif in polymer drug delivery systems - Pechar, Michal; Pola, Robert (Biotechnology advances, 2013)
The coiled coil is a superhelical structural protein motif that has been thoroughly investigated in recent years. Because of the relatively well-understood principles that determine the properties of coiled coil peptides and proteins, macromolecular systems containing the coiled coil motif have been suggested for various applications. This short review focuses on hybrid polymer coiled coil systems designed for drug delivery purposes. After a short introduction, the most important features of the coiled coils (stability, association number, oligomerization selectivity and orientation of helices) are described, and the factors influencing these characteristics are discussed. Several examples of the most interesting biomedical applications of the polymer-coiled coil systems (according to the authors' opinion) are presented.
Keywords: aminokyselinové motivy; hydrogely; Hydrogels; Models, Molecular; Protein Conformation; rekombinantní proteiny; rozpustnost; Amino Acid Motifs; Drug Delivery Systems; Recombinant Proteins; molekulární modely; lékové transportní systémy; konformace proteinů; Solubility